Effects of nutrient enrichment and crab herbivory on a SW Atlantic salt marsh productivity - Alberti, Juan (2011)
After intense debate it is now accepted that nutrients (a bottom-up process) and herbivores (a top-down process) are both important controls of plant productivity in many systems. Besides their direct effects, herbivores may also have profound positive or negative indirect effects that can be modulated by nutrients and time. The interactive relationships between time, nutrient availability and herbivore impacts (direct and indirect) on plant growth dynamics are an emerging research topic that merits further effort. Here we did several experiments in a SW Atlantic marsh to contribute towards that gap by focusing on the dominant plant, Spartina densiflora, and one of the dominant herbivores, the crab Neohelice (Chasmagnathus) granulata, in the marsh. Herbivory by the crab was highly seasonal, with most of the consumption occurring in fall. Even though crabs preferred nutrient enriched leaves, nitrogen content was not the driver of these seasonal variations. Crab herbivory had markedly indirect negative impacts on S. densiflora leaves, reducing their growth rates and increasing their senescence. These deleterious impacts may partially explain the seasonal decline in leaf growth and a net loss in leaf biomass observed in the fall. Fertilization did not seem to alter these processes. Adding nutrients increased leaf growth in the spring, where ambient herbivory was low, but it also increased herbivory in the fall, resulting in similar patterns as the ones observed under non-fertilized conditions. Herbivory by the crab also greatly affected the dynamics of S. densiflora stems. Increases in stem density in relation to initial conditions were larger in non-grazed than in grazed plots regardless of whether nutrients were added or not. Together, these results indicate that, in Southwestern marshes populated by S. densiflora and N. granulata, herbivory by the crab represents an important direct and indirect control of plant growth. Our results also emphasize the importance of considering impacts on growth rates and not only on biomass because not considering reduced growth after herbivory may lead to improper calculations of nutrient cycling or detritus production.